(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
A revolutionary interconnection of technology and criminal investigation, artificial intelligence (AI) in forensic medicine improves a number of procedures in the field. [...] The implications of these technologies in legal processes are seriously called into question by ethical issues about algorithmic bias, privacy, and the validity of AI-generated evidence.